Association Between Low-Density Lipoprotein Cholesterol and Platelet Distribution Width in Acute Ischemic Stroke - Yuan, Jian; Cai, Jian; Zhao, Pei; Zhao, Nan; Hong, Rong-Hua; Ding, Jie; Yang, Jin; Fan, Qing-Lei; Zhu, Jian; Zhou, Xia-Jun; Li, Ze-Zhi; Zhu, De-Sheng; et al. (Frontiers in Neurology, 2021)
Objective: Elevated low-density lipoprotein cholesterol (LDL-C) is an established risk factor for ischemic stroke; however, whether LDL-C affects the platelet deformation function in the peripheral blood circulation in patients with acute ischemic stroke (AIS) is unknown. The present study aimed to investigate the relationship between LDL-C and platelet distribution width (PDW) in AIS patients. Methods: We conducted a cross-sectional hospitalized-based study of consecutive 438 patients with AIS within 24 h. Blood samples were collected upon admission and prior to drug administration, and LDL-C and PDW (a parameter that reflects the heterogeneity of platelet volume) were assessed. The relationship between LDL-C and PDW were analyzed by linear curve fitting analyses. Crude and adjusted beta coefficients of LDL-C for PDW with 95% confidence intervals were analyzed using multivariate-adjusted linear regression models. Results: The PDW was significantly higher in the high LDL-C group compared with those in the normal LDL-C group (16.28 ± 0.37 fl vs. 16.08 ± 0.37 fl, p < 0.001). Adjusted smoothed plots suggested that there are linear relationships between LDL-C and PDW, and the Pearson's correlation coefficient (95%) was 0.387 (0.304–0.464, p < 0.001). The beta coefficients (95% CI) between LDL-C and PDW were 0.15 (0.12–0.18, p < 0.001) and 0.14 (0.11–0.18, p < 0.001), respectively, in AIS patients before and after adjusting for potential confounders. Conclusion: Our study suggested that the elevated LDL-C level was related to increased PDW among AIS patients.